Biological Potential of Carnivorous Plants from Nepenthales - Magdalena Wójciak; Marcin Feldo; Piotr Stolarczyk; Bartosz J. Płachno (Molecules, 2023)
Since Charles Darwin and his book carnivorous plants have aroused interest and heated debate. In addition, there is growing interest in this group of plants as a source of secondary metabolites and in the application of their biological activity. The aim of this study was to trace the recent literature in search of the application of extracts obtained from families Droseraceae, Nepenthaceae, and Drosophyllaceae to show their biological potential. The data collected in the review clearly indicate that the studied Nepenthales species have great biological potential in terms of antibacterial, antifungal, antioxidant, anti-inflammatory, and anticancer use. We proposed that further investigations should include: (i) bioactivity-guided investigations of crude plant extract to connect a particular type of action with a specific compound or a group of metabolites; (ii) a search for new bioactive properties of carnivorous plants; (iii) establishment of molecular mechanisms associated with specific activity. Furthermore, further research should be extended to include less explored species, i.e., Drosophyllum lusitanicum and especially Aldrovanda vesiculosa.